2017
DOI: 10.5603/kp.2017.0231
|View full text |Cite
|
Sign up to set email alerts
|

Zero-fluoroscopy catheter ablation of symptomatic pre-excitation from non-coronary cusp during pregnancy

Abstract: Current recommendations avoid the use of antiarrhythmic drugs in pregnancy and support catheter ablation (CA) due to symptomatic arrhythmias prior to pregnancy. Zero-fluoroscopy (ZF) mapping and navigation with three-dimensional electroanatomical mapping systems (3D-EAMS) allowed routine and safe non-fluoroscopic guidance of the procedure without X-ray exposure. We present the first case of a pregnant patient who underwent successful ZF CA of symptomatic pre-excitation from non-coronary cusp (NCC). A 24-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 0 publications
0
28
1
Order By: Relevance
“…However, even with a combination of 3D-EAM and ICE, complete ZF approach was followed only in a minority of patients. [2730] In contrast, our study showed ZF approach feasibility wherein even in the SHD group, procedural time could be reduced significantly, probably because of lesser time spent on detailed contour mapping and multichamber 3D mapping.…”
Section: Discussioncontrasting
confidence: 60%
“…However, even with a combination of 3D-EAM and ICE, complete ZF approach was followed only in a minority of patients. [2730] In contrast, our study showed ZF approach feasibility wherein even in the SHD group, procedural time could be reduced significantly, probably because of lesser time spent on detailed contour mapping and multichamber 3D mapping.…”
Section: Discussioncontrasting
confidence: 60%
“…Any dosage of X-ray is potentially harmful, as there is no threshold dose. A lower dosage of X-ray means a lower risk of potential harm for the embryo and various precautions are undertaken to minimize radiation exposure during invasive procedures in pregnancy [10]. In our patient, the late period of pregnancy (near its end) was an extenuating factor.…”
Section: Discussion and Review Of Literaturementioning
confidence: 71%
“…Routinely using ZF for CA may support this approach even for unfavorable locations and especially in pregnant patients. [11] Even rare and difficult anatomy could be effectively treated. Therefore the ZF approach could be used in experienced hands as a standard approach.…”
Section: Discussionmentioning
confidence: 99%